The impact of coagulation and division of drops on the parameters of the gas-drop turbulent jet - Yu.V. Zuev (Учёные записки Казанского университета: Серия Физико-математические науки)
This article is devoted to the definition of conditions under which the calculation of the gas-drop turbulent jet must be carried out with account of the interaction of drops. A mathematical model of the gas-liquid turbulent jet that considers the equations of coagulation and division of drops is presented. The relevance of the research is defined by the fact that many applied tasks in various areas of technology can be solved only by performing calculations with gas-liquid jets, the results of which may be doubtful at certain concentrations of the dispersed phase owing to the neglect of the collision of drops. As a result of the calculation by means of the obtained mathematical model of the gas-drop turbulent jet, three ranges of changes in the initial total volume concentration of drops corresponding to various impacts of the interaction of drops in the jet on its parameters are determined. The lack of influence of drops collisions on all parameters of the jet is characteristic of the first range. The second range differs by insignificant dependence of the speeds of phases on the coagulation of drops. The third range corresponds to the concentration of drops in the initial section of the jet at which there are intensive processes of coagulation and division of drops influencing all parameters of the jet. The following conclusions can be drawn from the results of the research: in the first and second cases, the equation of the mathematical model of the jet does not require to consider the interaction of drops to solve many applied problems; in the third case, it is obligatory to take account of the coagulation and crushing of drops.